Image à suivre - Philippe Dufour (Flaubert: Revue Critique et Génétique)
Flaubert belongs to the generation of lost images: no more romantic comparisons weaving correspondences and expressing the harmony of Creation. Mourning the sublime, Flaubert in Madame Bovary multiplies comparisons of a sadly grotesque nature. Here, drawing from Manfred Hardt’s example, we follow a series of images that punctuate Emma’s fate, around the bird motif deprived of its romantic prestige: it does not sing and has trouble flying.